Improving endurance performance among students through information technology - Kiryanova, L.A.; Polin, R.V.; Soprunov, N.I.; Pleskacheva, O.N. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate experimentally the influence of the use of smart watches and a mobile application on indicators of endurance and speed abilities of students in the process of physical education. Methods and structure of the study. The scientific work involved 100 students of higher educational institutions aged 18 to 22, studying in their 1st to 3rd year and admitted to physical education classes in the special medical group. The students were divided into experimental and control groups of 50 people each. The formative stage included the implementation of a pedagogical experiment lasting 8 weeks (2 months), during which the experimental group used smart watches and a mobile application to monitor physical activity, while the control group followed a traditional physical education programme without the use of digital tools. Results and conclusions. A comprehensive analysis of the results of the experimental study has made it possible to conclude that the use of smart watches and a mobile application has a multifactorial positive influence on students' physical fitness. The most pronounced effect was recorded in indicators of aerobic endurance, in functional indicators of the cardiovascular system, and in resistance to physical loads. Monitoring of load intensity, visualisation of progress and regular feedback contributed to the formation of a more rational motor regime in students of the experimental group.